Analisis Fenomenologis Pesan Dakwah Digital PCNU Pamekasan - Muhammad Ahnu Idris (Ulumuna: Jurnal Studi Keilsman, 2022)
The strong influence of social media in the lives of Indonesian people, requires preachers –both personal and institutional – to participate in filling this virtual world. Dai-dai arerequired to be able to use social media as a medium for delivering da'wah messages in aneffort to spread religious values. This da'wah model was later called "Digital Da'wah",which will be discussed in this article. This article discusses the Da'wah of the NahdlatulUlama (PCNU) Pamekasan Branch Manager through a fan page on Facebook socialmedia. Based on da'wah theories and a phenomenological approach, the research used in thisarticle is qualitative-descriptive. That is, the results of the research in this paper are presentedin the form of an elaboration based on the data found in the field. The primary data in thisstudy are uploads on the "Media NU Pamekasan" fanspage (created on November 7,2017). The results of the research contained in this article, PCNU Pamekasan utilizesdigital media as a means of preaching given the high number of social media users inIndonesia. This is considered effective in countering the teachings of radical groups who usesocial media to spread their understanding. There are two categories of da'wah messagesdelivered by PCNU Pamekasan through the two fanpages, namely sharia and morality